The impact of Communicative Language Teaching (CLT) Approach on Students’ Speaking Ability in a Public Indonesian University: Comparison between Introverts and Extrovert Groups - La Ode Nggawu; Nguyen Thi Phuong Thao (Universitas Negeri Makassar, 2023)
The aim of this research is to explore the effect of implementing the Communicative Language Teaching (CLT) Approach on the speaking ability of students-. The sample size for this study comprises 46 students representing the introvert class and the extrovert class, selected based on the results obtained from the distribution of questionnaires. To conduct the study, an experimental design was employed, which involved gathering quantitative data from the students' responses to the distributed questionnaire, as well as conducting pre-tests and post-tests to assess their speaking abilities. In order to analyze the collected data, the researcher utilized the SPSS program (Statistical Program for Social Science) for precise and efficient processing, generating various necessary outputs to draw meaningful conclusions. The findings of this study strongly indicate a positive impact of implementing the Communicative Language Teaching (CLT) model on the speaking abilities of introverted students. The results not only demonstrate the effectiveness of CLT in the speaking class but also align with previous research in the field. the incorporation of CLT in the speaking class positively impacts the speaking abilities of both introverted and extroverted students. However, a slight distinction can be observed in terms of the extent of improvement between the two groups, with the extrovert class showing a more notable progress. Recognizing and accommodating the diverse learning styles and preferences of students can help create a comprehensive and inclusive learning environment that fosters growth and development for all learners, regardless of their personality traits